Manure substitution for chemical nitrogen enhances soil quality without compromising maize yield: a short-term field experiment in Northeast China - Zhou, Chao; Wang, Jia; Xu, Ting; Pei, Kuan; Ma, Baoxin; Li, Qingchao; Liu, Yang; Ding, Xinying; Han, Yehui; Wang, Junqiang (Frontiers in Plant Science, 2025)
IntroductionManure substitution for chemical nitrogen has the potential to enhance crop yield, improve soil quality, and reduce environmental risks. Soil microorganisms perform critical functions in mediating soil nutrient cycling after the organic manure application. Nonetheless, how organic manure substitution regulates microbial communities to influence soil quality and crop yield remains unclear. MethodsA one-year field experiment comprising four organic manure substitution rates (25%, 50%, 75%, and 100%) along with a no-substitution control was conducted. Results and disscussionCompared to CK, only 25% substitution rate maintained maize yield, while 50‒100% manure substitution decreased maize yield by 15.9‒67.2%. This is primarily due to the decrease in root biomass (13.5‒29.1%), length (14.8‒43.3%), surface area (14.1‒48.8%) and volume (17.9‒53.4%). Manure substitution only increased soil quality index by 44‒55% in the 0-20 cm depth, mainly as a result of increased contents of soil organic C, total nitrogen, microbial biomass C and N, and enzyme activities. Moreover, manure substitution significantly increased the abundance of Actinobacteriota, Acidobacteriota, Gemmatimonadota, and Methylomirabiliota, with increases ranging from 12% to 101%. The strong correlations between these bacterial taxa and soil nutrient and C/N acquiring enzyme activities highlight their pivotal roles in boosting soil nutrients and enhancing soil quality. Therefore, organic manure substitution can be a sustainable fertilizer regime to enhance soil quality and maintain maize yield in Northeast China, and the optimal substitution rate is 25%.